2020
DOI: 10.1038/s41598-020-73250-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrode-free visual prosthesis/exoskeleton control using augmented reality glasses in a first proof-of-technical-concept study

Abstract: In the field of neuroprosthetics, the current state-of-the-art method involves controlling the prosthesis with electromyography (EMG) or electrooculography/electroencephalography (EOG/EEG). However, these systems are both expensive and time consuming to calibrate, susceptible to interference, and require a lengthy learning phase by the patient. Therefore, it is an open challenge to design more robust systems that are suitable for everyday use and meet the needs of patients. In this paper, we present a new conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…This requires that the user of the prosthesis have a healthy hand with which he can operate the two buttons on the remote control. A novel approach to electrodeless visual control of the orthosis with augmented reality glasses can counteract this [11,12], which is worth testing.…”
Section: Discussionmentioning
confidence: 99%
“…This requires that the user of the prosthesis have a healthy hand with which he can operate the two buttons on the remote control. A novel approach to electrodeless visual control of the orthosis with augmented reality glasses can counteract this [11,12], which is worth testing.…”
Section: Discussionmentioning
confidence: 99%
“…[ 91 , 92 , 93 ] In addition, exoskeletons and prostheses linked with the XR platforms can increase rehabilitation efficiency and enable remote training. [ 94 , 95 , 96 ] A customized exoskeleton with cost‐effective fabrication and low power consumption has been developed to detect and display the joint movements of users ( Figure 6 a ). [ 97 ] The triboelectric bidirectional sensors embedded in the exoskeleton monitor multidimensional motions such as rotation, twisting, and linear motion.…”
Section: Metaverse Wearables Coupled With Xr Technologymentioning
confidence: 99%
“…The results indicated a decrease in recovery time for patients undergoing training with AR technology. Hazubski et al (2020) demonstrated the application of AR glasses for tracking hand exoskeleton movements. The AR glass is used along with a monocular camera to track the movements.…”
Section: Exoskeletons User Training Advancementsmentioning
confidence: 99%